Removal of Methyl Orange from Aqueous Solutions by Adsorption Using Corn Leaves as Adsorbent Material (Journal of Engineering, 2019)
A comparative study was done on the adsorption of methyl orange dye (MO) using non-activated and activated corn leaves with hydrochloric acid as an adsorbent material. Scanning electron microscopy (SEM) and Fourier Transform Infrared spectroscopy (FTIR) were utilized to specify the properties of adsorbent material. The effect of several variables (pH, initial dye concentration, temperature, amount of adsorbent and contact time) on the removal efficiency was studied and the results indicated that the adsorption efficiency increases with the increase in the concentration of dye, adsorbent dosage and contact time, while inversely proportional to the increase in pH and temperature for both the treated and untreated corn leaves. The equilibrium data is best fitted to Freundlich isotherm for untreated adsorbent, while Langmuir isotherm show best agreement with the data when the treated adsorbent is used. The rate of adsorption was found to follow the pseudo first order kinetic model (PFO) when non-activated adsorbent is used, while the pseudo second order model (PSO) is fitted to the adsorption data using activated adsorbent.